2007
DOI: 10.1176/ajp.2007.164.4.617
|View full text |Cite
|
Sign up to set email alerts
|

Increased Waking Salivary Cortisol Levels in Young People at Familial Risk of Depression

Abstract: Hypersecretion of cortisol can be detected in asymptomatic individuals at genetic risk of depression and may represent an illness endophenotype. Further studies will be needed to find out if increased waking salivary cortisol levels can predict individual risk of illness and whether the increased cortisol secretion has implications for general health and cognitive function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
71
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 152 publications
(86 citation statements)
references
References 41 publications
13
71
0
1
Order By: Relevance
“…Indeed, post hoc analyses showed that CAR was a predictor of elevated depressive symptoms at 6 months post-treatment for women with low depressive symptoms at the baseline assessment, but not for women with high symptoms at baseline. This would be consistent with the observation that individuals with remitted depression demonstrated a larger cortisol awakening response than non-depressed controls (59), and asymptomatic young adults at familial risk for depression exhibit larger CAR than those without family history of depression (60). This is also consistent with a long-standing conceptualization that hypersecretion of CRH, the initial hormone in the HPA cascade, represents an endophenotype for internalizing psychopathology risk, whereas persistence and severity of different types of psychopathology (e.g., depression and PTSD) are associated with diverging patterns of HPA-axis dysregulation (61).…”
Section: Discussionsupporting
confidence: 89%
“…Indeed, post hoc analyses showed that CAR was a predictor of elevated depressive symptoms at 6 months post-treatment for women with low depressive symptoms at the baseline assessment, but not for women with high symptoms at baseline. This would be consistent with the observation that individuals with remitted depression demonstrated a larger cortisol awakening response than non-depressed controls (59), and asymptomatic young adults at familial risk for depression exhibit larger CAR than those without family history of depression (60). This is also consistent with a long-standing conceptualization that hypersecretion of CRH, the initial hormone in the HPA cascade, represents an endophenotype for internalizing psychopathology risk, whereas persistence and severity of different types of psychopathology (e.g., depression and PTSD) are associated with diverging patterns of HPA-axis dysregulation (61).…”
Section: Discussionsupporting
confidence: 89%
“…However, the associations are likely attributable to the fact that the two conditions share several neurobiological pathways including hypothalamic-pituitary-adrenal (HPA) axis alterations, elevations in pro-inflammatory cytokines, and decreased serotonergic tone [27]. Sleep disorders have been reported to lead to alterations in HPA axis hormones, such as adrenocorticotropic hormone (ACTH) and cortisol [2729]. Alterations of the HPA axis, observed among individuals with suicidal ideation and depressive disorders, may well be one mechanism underlying the consistently observed statistical association of sleep disturbance and suicidal ideation.…”
Section: Discussionmentioning
confidence: 99%
“…In comparison to the other two groups, participants who consumed B-GOS showed a significantly reduced waking-cortisol response . Exaggerated waking cortisol is a biomarker of emotional disturbances such as depression 45, 46. Furthermore, participants completed an emotional dot-probe task that measures vigilance, or attention to negative stimuli, which is also a behavioural marker of anxiety and depression [47].…”
Section: Human Researchmentioning
confidence: 99%